Fintech, Business, and Development (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
Fintech, short for financial technology, has become an increasingly important player in the global economy. Fintech companies leverage technological advancements to offer innovative financial services, ranging from mobile banking and peer-to-peer lending to cryptocurrency and blockchain-based solutions. By leveraging digital technologies, fintech firms have offered financial services to previously excluded populations, enabling individuals to access credit, insurance, and savings products that were previously unavailable to them. By providing alternative sources of financing, such as peer-to-peer lending and crowdfunding, fintech has enabled small businesses to access capital that they may not have been able to obtain through traditional sources. This has led to increased investment, innovation, and job creation, all of which are essential for economic growth. Moreover, fintech has improved the efficiency and transparency of financial markets, reducing costs and improving accessibility for investors. Consequently, new financial instruments, such as cryptocurrencies and digital securities, have been developed, offering greater flexibility and transparency than traditional financial products. In conclusion, fintech has played a crucial role in driving economic and financial development, promoting financial inclusion, and enhancing firm performance. As the world continues to embrace digital technologies, fintech is poised to play an even greater role in shaping the future of finance.